HUBUNGAN INDONESIA-TIONGKOK DALAM PERSPEKTIF KEBIJAKAN PUBLIK DAN DIPLOMASI EKONOMI: ANALISIS BELT AND ROAD INITIATIVE - Ahyadi, Khairul (Cahaya Ilmu Bangsa, 2025)
This article analyzes Indonesia-China relations from the perspective of public policy and economic diplomacy with a focus on the implementation of the Belt and Road Initiative (BRI). Indonesia has a strategic role in the Belt and Road Initiative (BRI) initiated by China. As one of the main partners, Indonesia benefits from investment and infrastructure development supported by the BRI. However, this cooperation also poses challenges, especially related to public policy regulations, transparency, and long-term impacts on the national economy. Using a qualitative approach based on literature studies, this article analyzes how Indonesian public policy responds to BRI investments. The Indonesian government has adopted various strategies to maximize the benefits of this cooperation, such as encouraging infrastructure projects that are in line with the National Medium-Term Development Plan (RPJMN) and improving foreign investment regulations to remain profitable for domestic interests. In addition, the dimensions of economic diplomacy in Indonesia-China cooperation have also developed, covering the sectors of trade, infrastructure, and economic security. The BRI has become an important tool in strengthening bilateral relations, although it has also raised concerns regarding economic dependence and imbalances in the trade balance. Therefore, adaptive public policies and careful economic diplomacy strategies are needed so that Indonesia can optimize the benefits of this cooperation. With in-depth analysis, this study provides insights into the implications of policy and economic diplomacy in the implementation of BRI in Indonesia. Artikel ini menganalisis hubungan Indonesia-Tiongkok dalam perspektif kebijakan publik dan diplomasi ekonomi dengan fokus pada implementasi Belt and Road Initiative (BRI). Indonesia memiliki peran strategis dalam Belt and Road Initiative (BRI) yang digagas oleh Tiongkok. Sebagai salah satu mitra utama, Indonesia memperoleh manfaat dari investasi dan pembangunan infrastruktur yang didukung oleh BRI. Namun, kerja sama ini juga menimbulkan tantangan, terutama terkait dengan regulasi kebijakan publik, transparansi, serta dampak jangka panjang terhadap perekonomian nasional. Dengan pendekatan kualitatif berbasis studi literatur, artikel ini menganalisis bagaimana kebijakan publik Indonesia merespons investasi BRI. Pemerintah Indonesia mengadopsi berbagai strategi untuk memaksimalkan keuntungan dari kerja sama ini, seperti mendorong proyek infrastruktur yang selaras dengan Rencana Pembangunan Jangka Menengah Nasional (RPJMN) dan meningkatkan regulasi investasi asing agar tetap menguntungkan bagi kepentingan domestik. Selain itu, dimensi diplomasi ekonomi dalam kerja sama Indonesia-Tiongkok juga berkembang, mencakup sektor perdagangan, infrastruktur, dan keamanan ekonomi. BRI menjadi alat penting dalam memperkuat hubungan bilateral, meskipun juga menimbulkan kekhawatiran terkait ketergantungan ekonomi serta keseimbangan dalam neraca perdagangan. Oleh karena itu, kebijakan publik yang adaptif dan strategi diplomasi ekonomi yang cermat diperlukan agar Indonesia dapat mengoptimalkan manfaat dari kerja sama ini. Dengan analisis yang mendalam, studi ini memberikan wawasan mengenai implikasi kebijakan dan diplomasi ekonomi dalam implementasi BRI di Indonesia.